Proposed Design of a Mobile Lift Device to Reduce the Risk of Musculoskeletal Injuries Among Fire Extinguisher Inspectors - Yonlada Khunburan; Teeraphun Kaewdok (Safety, 2025)
Fire extinguisher inspectors face ergonomic risk factors and are exposed to several musculoskeletal disorders (MSDs). The aim of this study was to design and evaluate a mobile lift device to reduce the risk of musculoskeletal injuries among fire extinguisher inspectors. This was followed by a quasi-experimental trial among 28 workers, using surface electromyography (EMG), in which muscle activity with percentage of maximum voluntary contraction (MVC), postural analysis using the Rapid Entire Body Assessment (REBA), perceived exertion, and perceived ease of use among workers were evaluated during the fire extinguisher inspection process employing a manual fire extinguisher and using a mobile lift device. The results of the EMG measurement of the muscle activity in the biceps brachii, triceps brachii, middle deltoid, and upper trapezius were obtained using the MVC parameter. The MVC parameter was employed to normalize the EMG signals, allowing for a standardized comparison of muscle activation levels across different tasks and conditions. The results showed a significant positive effect on the muscle activity of the middle deltoid and biceps brachii; the posture risk level and rating for perceived exertion with the mobile lift device were generally lower than those of manual lifting (p < 0.001). With the mobile lift device, there was significant reduction in the muscle activity of the triceps brachii and upper trapezius (p < 0.05). Accordingly, mobile lift devices were found to be useful due to the reduced muscle effort, and postural risks were reduced when using the mobile lift device. Further studies are needed for modifications to the lift assist device based on ergonomic measures of muscle activity and user tests by adjusting the task to suit the capabilities of workers.